2014
DOI: 10.1016/j.neuron.2014.01.044
|View full text |Cite|
|
Sign up to set email alerts
|

Delta Opioid Receptors Presynaptically Regulate Cutaneous Mechanosensory Neuron Input to the Spinal Cord Dorsal Horn

Abstract: SUMMARY Cutaneous mechanosensory neurons detect mechanical stimuli that generate touch and pain sensation. Although opioids are generally associated only with the control of pain, here we report that the opioid system in fact broadly regulates cutaneous mechanosensation, including touch. This function is predominantly subserved by the delta opioid receptor (DOR), which is expressed by myelinated mechanoreceptors that form Meissner corpuscles, Merkel cell-neurite complexes, and circumferential hair follicle end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
76
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 61 publications
16
76
0
Order By: Relevance
“…It is, however, still unclear whether DORs are differentially expressed in mechanical vs. heat sensitive primary afferent fibres terminating in the superficial layers I and II of the spinal dorsal horn. Depending on the experimental approach, DOR receptors have been found largely in peptidergic fibres [3;21;48], in a small subset of non-peptidergic C-fibres and myelinated A-fibres [4;42], or not at all at DRG neuron membranes of naïve animals [6;9]. Our functional approach now revealed that none of the investigated fibre types was considerably inhibited by saturating concentrations of the DOR agonist SNC80.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is, however, still unclear whether DORs are differentially expressed in mechanical vs. heat sensitive primary afferent fibres terminating in the superficial layers I and II of the spinal dorsal horn. Depending on the experimental approach, DOR receptors have been found largely in peptidergic fibres [3;21;48], in a small subset of non-peptidergic C-fibres and myelinated A-fibres [4;42], or not at all at DRG neuron membranes of naïve animals [6;9]. Our functional approach now revealed that none of the investigated fibre types was considerably inhibited by saturating concentrations of the DOR agonist SNC80.…”
Section: Discussionmentioning
confidence: 97%
“…They seem to express the TRPM8 channel [13] and could be muscle afferents (R. P. Seal, unpublished observations) or epidermal free nerve endings [30]. Interestingly, TH + DRG neurons have recently been shown not to express MORs [4]. Considering the lack of inhibition by DAMGO observed in most VGluT3 + C-fibres innervating lamina II neurons (present study), this suggests that the population of VGluT3 + C-fibres innervating lamina II neurons could be C-LTMRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*p Ͻ 0.05; **p Ͻ 0.01; ***p Ͻ 0.001. Scale bar, 100 m. We next examined the neurotrophin receptor TrkC, as it is expressed by SAIs and other DRG neurons, including proprioceptors (Airaksinen et al, 1996). Before touch dome innervation at E13.5 and shortly after innervation at E16.5, the percentages of TrkC ϩ and TrkB ϩ TrkC ϩ DRG neurons were equivalent in K14; Atoh1 CKO mice and control littermates ( Fig.…”
Section: Drg Neuron Numbers Are Normal In Mice That Lack Merkel Cellsmentioning
confidence: 99%
“…This is an important consideration because the cell-autonomous and non-cellautonomous mechanisms that control SAI molecular phenotype, peripheral projection morphology, and electrophysiological function are unknown. Importantly, multiple lines of evidence suggest that SAI neurons respond to BDNF and NT3 signaling, presumably through the expression of TrkB and TrkC (Airaksinen et al, 1996;Albers et al, 1996;Fundin et al, 1997;Carroll et al, 1998;LeMaster et al, 1999;Cronk et al, 2002;Szeder et al, 2003;Krimm et al, 2004). These observations raise the possibility that Merkel cell-derived neurotrophins might play a role in directing SAI neuron maturation.…”
Section: Introductionmentioning
confidence: 99%